Inhibitory Effects of Lipopeptides and Glycolipids on C. albicans–Staphylococcus spp. Dual-Species Biofilms - Ceresa, Chiara; Rinaldi, Maurizio; Tessarolo, Francesco; Maniglio, Devid; Fedeli, Emanuele; Tambone, Erica; Caciagli, Patrizio; Banat, Ibrahim M.; Diaz De Rienzo, Mayri Alessandra; Fracchia, Letizia (Frontiers in Microbiology, 2021)
Microbial biofilms strongly resist host immune responses and antimicrobial treatments and are frequently responsible for chronic infections in peri-implant tissues. Biosurfactants (BSs) have recently gained prominence as a new generation of anti-adhesive and antimicrobial agents with great biocompatibility and were recently suggested for coating implantable materials in order to improve their anti-biofilm properties. In this study, the anti-biofilm activity of lipopeptide AC7BS, rhamnolipid R89BS, and sophorolipid SL18 was evaluated against clinically relevant fungal/bacterial dual-species biofilms (Candida albicans, Staphylococcus aureus, Staphylococcus epidermidis) through quantitative and qualitative in vitro tests. C. albicans–S. aureus and C. albicans–S. epidermidis cultures were able to produce a dense biofilm on the surface of the polystyrene plates and on medical-grade silicone discs. All tested BSs demonstrated an effective inhibitory activity against dual-species biofilms formation in terms of total biomass, cell metabolic activity, microstructural architecture, and cell viability, up to 72 h on both these surfaces. In co-incubation conditions, in which BSs were tested in soluble form, rhamnolipid R89BS (0.05 mg/ml) was the most effective among the tested BSs against the formation of both dual-species biofilms, reducing on average 94 and 95% of biofilm biomass and metabolic activity at 72 h of incubation, respectively. Similarly, rhamnolipid R89BS silicone surface coating proved to be the most effective in inhibiting the formation of both dual-species biofilms, with average reductions of 93 and 90%, respectively. Scanning electron microscopy observations showed areas of treated surfaces that were free of microbial cells or in which thinner and less structured biofilms were present, compared to controls. The obtained results endorse the idea that coating of implant surfaces with BSs may be a promising strategy for the prevention of C. albicans–Staphylococcus spp. colonization on medical devices, and can potentially contribute to the reduction of the high economic efforts undertaken by healthcare systems for the treatment of these complex fungal–bacterial infections.